Perencanaan Sistem Proteksi Petir Pada Kawasan Candi Borobudur - Ragil Triyanto; Sapto Nisworo; Hery Teguh Setiawan (CV. Ulil Albab Corp, 2022)
BMKG data for 2020-2021 shows that Magelang Regency has an average of 540,000-720,000 lightning strikes per year. The installation of a lightning protection system aims to avoid, prevent and reduce the danger posed by lightning strikes. The Borobudur Temple area zone 1 and zone 2 is the center of a world tourist destination, namely the UNESCO historical monument of Borobudur Temple with an area that requires lightning protection of 617,200 m2. The lightning protection method used in this study is the E.S.E (Early Streamer Emission) lightning protection system. The results obtained in this study are in the form of a radius of protection with an air terminal of the Kurn R-150 brand of 70,650 meters2 for each unit of the protection system. It takes 12 units of a lightning protection system to protect all areas of zone 1 and zone 2 that require a protection system. Ground resistance < 5Ω is obtained with one electrode rod 3 meters long for each unit according to the standards of SNI 03-7015-2004, PUIL, and PUIPP. The cost plan ordered for the lightning protection system in the Borobudur Temple area is IDR 302,171,781 with 11% VAT IDR 335,410,677.